Territorio, sociedad y poder en los Andes de Huamalíes-Huánuco La transición política de villa a ciudad en Llata, siglos XIX-XX - Espinoza Claudio, Cesar (2006)
This report contains a general vision of the social and political processes that were experienced by the communities, villages and cities located in the high Andean area of Huanuco. We examine, in particular, the microregion of Huamalíes near the Marañon river whose communities practice a seasonal agriculture on small plots associated with complex dynamic systems of migration toward surrounding mining areas and the coca rainforest of Monson. During the nineteenth and twentieth centuries two social groups emerge and consolidate with hegemonic power: Llata and La Union. The democratic and authoritarian options are expressed and diffused to the interior of the urban nuclei that evolve from villages to cities in their desire to be connected to the national oligarchical power and to conquer basic services in order to modernize their regional economies.